Analysis of Factors That Interrupt With INR Control in the First Anticoagulation Clinic Monitoring Jordanian Patients - Nairooz H. Al-Momany MSc (Clinical and Applied Thrombosis/Hemostasis, 2019)
Multiple factors such as vitamin K consumption, drug interactions, herbs interactions, disease states, and alcohol intake affect international normalized ratio (INR) values and thus warfarin dosing. These variables have been described in general and for all patients in the literature. In contrast, the factors that affect INR control in a specific population are rarely studied. Being aware of these factors contributes a lot in maintaining an INR control and avoiding the supratherapeutic or subtherapeutic anticoagulation and the associated risks of hemorrhage or thromboembolism. The aim of this study is to recognize the specific population factors in Jordanian patients that interrupt INR control. Such recognition provides clinical pharmacists managing the anti-coagulation clinic (ACC) with necessary tools and predictors of dose adjustment, nontarget INR handling, and points to add on to the educational session. A total of 2788 patients were referred to the first clinical pharmacists managed ACC at Queen Alia Heart Institute—the only official referral hospital for cardiac patients in Jordan—for education and monitoring between November 1, 2013, and November 1, 2016. We evaluated specific population factors that interrupt INR control using a pretested, structured clinical data collection form. The patients were followed up regularly for achieving target INR (TINR). For patients who were not achieving TINR, the possible cause was examined thoroughly by reviewing the patient’s medical file for recent medication intake, comorbidities, and laboratory results. Then the patients or their caregiver were asked direct questions regarding their diet, food supplements, cigarette smoking, shisha smoking, alcohol intake, herbs, and complementary medicine use and compliance, in addition to performing pharmacogenetic testing (polymorphisms of vitamin K–epoxide reductase complex [VKORC1] and cytochrome P450 2C9 [CYP2C9] genes) in special cases. For a total of 2788 patients, 89 488 INR values were included in the study. Of all, 20 365 (22.8%) were non-TINR values, 13 145 (14%) were subtherapeutic, and 7220 (8.1%) were supratherapeutic. All patients included in the study had a non-TINR at least 3 times (n = 65, 2.3%) and as frequent as 50 times (n = 21, 0.8%) during the study period. Non-TINR values ranged from 1 to 11. Serious side effects reported in 7 patients with uncontrolled INR, 6 were bleeding, which required hospitalization (2 upper gastrointestinal [GI] bleeding, 3 nasal bleeding, and 1 eye bleeding), 1 was cerebrovascular accident (CVA thrombolytic). Factors that interrupted INR control in our population, arranged in descending sequence, were concurrent medication use 46.9% (mainly Salicylates and Amiodarone), smoking cigarettes and shisha 17% (represented the most frequent single factor that caused non-TINR in the present study), a nonbalanced dietary vitamin K intake 16.88% caused changes in INR (lower) was related to an increase in the intake of vitamin K-rich food, were noticed to be much more in the spring season in Jordan (end of March and April mainly), herbal supplements 15.02%; Hawthorn (Crataegus, الزعرور) is an herb that lives widely in Jordan, and shockingly we found that it is used very commonly in our ACC patients and corresponded to an elevated INR <8 in 11 patients, and serious bleeding events that required hospitalization in 2 cases), noncompliance 1.49%, comorbid diseases 1%, malabsorption 0.53%, alcohol intake 0.39%, and VKORC1 A/G and CYP2C9 *1*1 genotype 0.15%. The analysis of factors that interrupted with INR control in our patients were both predicted and distinctive; most of these factors were reported previously by other researchers. On the other hand, many of the previously reported factors were not frequently detected in our patients, and the frequency of each of the realized factors was contributed differently to non-TINR in our population. Alarming factors causing non-TINR detected in our study include smoking both cigarettes and shisha, herbal use (Hawthorn and Ginseng), increased intake of vitamin K rich food in the spring season, and concurrent medication use (Salicylates, Amiodarone, Ciprofloxacin, nonsteroidal anti-inflammatory drugs [NSAIDS], Azithromycin, Clarithromycin: although the use of these drugs is mandatory sometimes, it can be replaced by an alternative, eg, antibiotics or monitored closely together with warfarin).